Determining the rainfed arable production potential of climatically marginal land in the Northwest Province using the Cyslamb Land Evaluation Model - Laker, M.C. (Michiel Christiaan), 1939- (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Land-Use Planning))--University of Pretoria, 2008.